2005
DOI: 10.1021/es048327d
|View full text |Cite
|
Sign up to set email alerts
|

Summertime Ambient Formaldehyde in Five U.S. Metropolitan Areas:  Nashville, Atlanta, Houston, Philadelphia, and Tampa

Abstract: First, we briefly review the atmospheric chemistry and previous intercomparison measurements for HCHO, with special reference to the diffusion scrubber Hantzsch reaction based fluorescence instrument used in the field studies reported herein. Then we discuss summertime HCHO levels in five major U.S. cities measured over 1999-2002, primarily from ground-based measurements. Land-sea breeze circulations play a major role in observed concentrations in coastal cities. Very high HCHO peak mixing ratios were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 71 publications
3
54
0
Order By: Relevance
“…Relatively stable at night, HCHO rapidly photolyzes after sunrise and serves as an important source for early morning radicals. Some of the highest HCHO levels in North America have been reported for the HGA, in particular the HSC area, ranging from ∼35 to 52 ppbv (Dasgupta et al, 2005;Eom et al, 2008). Airborne HCHO measurements in HGA likewise exceeded 30 ppbv on some occasions; terminal olefins were identified as the most important precursors .…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Relatively stable at night, HCHO rapidly photolyzes after sunrise and serves as an important source for early morning radicals. Some of the highest HCHO levels in North America have been reported for the HGA, in particular the HSC area, ranging from ∼35 to 52 ppbv (Dasgupta et al, 2005;Eom et al, 2008). Airborne HCHO measurements in HGA likewise exceeded 30 ppbv on some occasions; terminal olefins were identified as the most important precursors .…”
Section: Introductionmentioning
confidence: 93%
“…It is likely that thus a shallow layer existed between the boundary height and the height where the wind shear occurred, which predominantly contained air masses which have passed the HSC area before arriving the Moody Tower area. There have been indications for stratified SO 2 plumes aloft based on early morning ozone sonde launchings (Rappenglück et al, 2008), others have previously observed simultaneously elevated SO 2 and HCHO at HSC (Dasgupta et al, 2005) tial Optical Absorption Spectroscopy (DOAS) at the Moody Tower for 14 September 2009. They report elevated SO 2 mixing ratios along the upper light path (130-300 m a.g.l.)…”
Section: Illustrative Examples For Regression Model Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…In the continental boundary layer, HCHO concentrations of the order of a few parts per billion by volume (ppbv) are reported and can reach values greater than 10 ppbv in large cities (Dasgupta et al, 2005) and tropical regions (Kesselmeier et al, 2002). The HCHO concentration falls below 0.5 ppbv far from the sources in the oceanic background atmosphere for example (e.g., Heikes et al, 2001;, 2003aFrost et al, 2002).…”
Section: Introductionmentioning
confidence: 99%